2020
DOI: 10.1038/s41598-020-69764-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of benzylidenemalononitrile by Knoevenagel condensation through monodisperse carbon nanotube-based NiCu nanohybrids

Abstract: Monodisperse nickel/copper nanohybrids (nicu@MWcnt) based on multi-walled carbon nanotubes (MWcnt) were prepared for the Knoevenagel condensation of aryl and aliphatic aldehydes. the synthesis of these nanohybrids was carried out by the ultrasonic hydroxide assisted reduction method. nicu@MWcnt nanohybrids were characterized by analytical techniques such as X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (teM), high-resolution transmission electron microscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Another example of bimetallic catalyst was monodisperse nickel/copper nanohybrids (NiCu@MWCNT) based on multi-walled carbon nanotubes (MWCNT) that was used at rt in water/methanol (1/1) in short reaction times (entry 20). [51] Recycling procedure was also performed with 4-nitrobenzaldehyde. Under these conditions, this reaction gave complete conversion when carried out in the absence of a catalyst.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of bimetallic catalyst was monodisperse nickel/copper nanohybrids (NiCu@MWCNT) based on multi-walled carbon nanotubes (MWCNT) that was used at rt in water/methanol (1/1) in short reaction times (entry 20). [51] Recycling procedure was also performed with 4-nitrobenzaldehyde. Under these conditions, this reaction gave complete conversion when carried out in the absence of a catalyst.…”
Section: Discussionmentioning
confidence: 99%
“…However, under the adopted condition, after 8 min at rt in water/methanol we obtained a precipitate which was filtered and collected indicating that this substrate gave complete conversion without catalyst. Another example of bimetallic catalyst was monodisperse nickel/copper nanohybrids (NiCu@MWCNT) based on multi‐walled carbon nanotubes (MWCNT) that was used at rt in water/methanol (1/1) in short reaction times (entry 20) [51] . Recycling procedure was also performed with 4‐nitrobenzaldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…[11] One such approach is the condensation between a carbonyl compound and an active methylene moiety-possessing molecule with the utilization of a wide variety of catalysts including mesoporous materials, metal-organic frameworks, bimetallic, mixed oxide, graphitic carbon nitride, and deep eutectic solvents. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Further, hazardous solvents including tetrahydrofuran, [32,33] dimethyl formamide, [34] alcohols, [35,36] dioxane, [37] toluene, [38] acetonitrile, [39] and dichloromethane [40] have often been used to effect this carbon-carbon bond construction. [41][42][43][44][45][46][47] For instance, Hassan et al [41] showed the capacity of amino-grafted graphene oxide-Fe 3 O 4 in tetrahydrofuran at 50 C, Markad et al [44] exposed the performance of amidefunctionalized 2D coordination polymer (involving a bis-pyridylmethyldiaminobutane diacetamide) in methanol, Taher et al [45] revealed the amine-functionalized metal-organic framework in DMF, Zhong et al [46] discovered the utility of bifunctional mesoporous carbon nitride in toluene at 80 C under ...…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we proposed new chromospheres based on the benzylidene scaffold . This type of compound has a simple structure that is easy to modify also due to the simplicity of the synthesis . This leads to the possibility of fine-tuning the spectral properties of the chromophore and then the iodonium salt.…”
Section: Introductionmentioning
confidence: 99%
“…44 This type of compound has a simple structure that is easy to modify also due to the simplicity of the synthesis. 45 This leads to the possibility of fine-tuning the spectral properties of the chromophore and then the iodonium salt. Most of the benzylidene-based iodonium salts presented there were characterized by an absorption band located at about 360 nm.…”
Section: Introductionmentioning
confidence: 99%